Pengaruh Koneksi Politik terhadap Audit Fee - Mahendra, Zelldy Alex; Cheisviyanny, Charoline (Jurnal Nuansa Karya Akuntansi, 2023)
This study examines the influence of political connections with the control variables of company size, debt equity ratio and profitability on audit fees for BUMN companies in Indonesia for the 2018-2022 period. The sample was determined by purposive sampling method and 32 BUMN companies were obtained as sample. The type of used is secondary data using multiple linear regression analysis. The results of the study are that political connections influence audit fees. The control variable company size has an effect on audit fees, while debt equity ratio and profitability have no effect on audit fees.